A rapid probability estimator and binary arithmetic coder - Withers, W.D. (IEEE transactions on information theory, 2001)
We present a new integrated algorithm for binary arithmetic coding and probability estimation, competitive in speed and compression performance with state-of-the-art algorithms such as the QM-coder and Z-coder. The chief innovation is representing the bracketing interval width both directly and by a logarithmic approximation. Performance is evaluated by experiments using bilevel-image data sets. An open-source software version is available.